2018
DOI: 10.1001/jamaoto.2018.2049
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Risk Factors Associated With Unplanned Reoperation in Major Head and Neck Surgery

Abstract: IMPORTANCE Understanding the preoperative, intraoperative, and postoperative risk factors of reoperation is the optimal way to approach decreasing its incidence. OBJECTIVE To identify risk factors of unplanned reoperation following major operations of the head and neck. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study queried the American College of Surgeons National Surgical Quality Improvement Program database and identified 2475 cases of major operations of the head and neck performed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
6
15
0
1
Order By: Relevance
“…In univariate analysis, anoplasty (OR 0.13; p = 0.04), enterectomy (OR 5.11; p < 0.01), duration of intraoperative hypothermia (OR 1.01; p = 0.01), and the length of operative time (OR 1.01; p < 0.01) were significantly associated with unplanned reoperation. However, our multivariate regression analyses identified that the only factor associated with unplanned reoperation was prolonged operative time, which was consistent with previous research [ 16 ]. In plastic surgery, an association between increasing operative time and incidence of unplanned reoperation had been confirmed [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In univariate analysis, anoplasty (OR 0.13; p = 0.04), enterectomy (OR 5.11; p < 0.01), duration of intraoperative hypothermia (OR 1.01; p = 0.01), and the length of operative time (OR 1.01; p < 0.01) were significantly associated with unplanned reoperation. However, our multivariate regression analyses identified that the only factor associated with unplanned reoperation was prolonged operative time, which was consistent with previous research [ 16 ]. In plastic surgery, an association between increasing operative time and incidence of unplanned reoperation had been confirmed [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…In plastic surgery, an association between increasing operative time and incidence of unplanned reoperation had been confirmed [ 10 ]. And Sangal et al had revealed that a greater total operation time was associated with an unplanned reoperation in major operations of the head and neck [ 16 ]. These results could be interpreted as a more complex surgical procedure would be more likely to require unplanned reoperation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been many studies investigating short‐term morbidity and mortality associated with head and neck cancer surgeries, including TL. Such studies have investigated factors associated with need for reoperation, 11,12 30‐day unplanned readmission, 13‐18 30‐day mortality, 19 and prolonged inpatient LOS. Those investigating LOS include reviews of institutional 20 and national database 16,19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned reoperation was defined by the US NSQIP database as an “unplanned return to the operating room for a surgical procedure related to either the index or concurrent procedure performed” [ 4 ]. Earlier studies have found that colorectal operations account for the greatest proportion of unplanned reoperations.…”
Section: Introductionmentioning
confidence: 99%